Capacidad de producción de aguaje para la exportación de la pulpa al mercado español - Del Castillo Gonzales, Milagros Gabriela (2022)
The general objective of the research was to analyze the production capacity of aguaje in the Loreto region for the export of pulp to the Spanish market. The methodology that has been used for the development of the research was descriptive, with a quantitative approach with a non-experimental design. A sample of 291 farmers was taken, to whom the survey was applied as a technique and as an instrument the questionnaire of questions and data collection sheet for the collection of numerical information. In the results, it has been possible to characterize the production of aguaje, since the highest rate of population dedicated to agriculture is 41 - 50 years old, most of them are male, also, in the production process, the majority of farmers are dedicated to cultivation for 20 years; As for the harvest, farmers use the climber technique; in the post-harvest, it was identified that the majority of farmers sell unprocessed aguaje, due to a greater demand for fresh fruit; Finally, in the marketing of aguaje, they sell it by the kilo with a value of seven soles, although it varies frequently.